The Making of Aloe vera Powder (Aloe vera L.) with Foam-mat Drying Method - Ramadhia, Muflihah; Kumalaningsih, Sri; Santoso, Imam (Jurnal Teknologi Pertanian, 2012)
Aloe vera gel contains nutrients that are complex but easily damaged so it is deemed necessary for further processing into high value products such as powder. The study was conducted to determine the combination of the concentration of the filler (maltodextrin) and foaming agent (tween 80) is right in making a quality aloe vera powder using foam-mat drying. The design of the study is a randomized block design of two factors, namely the concentration of maltodextrin (5%, 10%, 15 %) and the concentration of tween 80 (0.1%, 0.2%, 0.3%). The best Aloe vera powder is obtained at a concentration of 15% maltodextrin and 0.3% tween 80, which composition of the water content 10.28%, the activity of free radicals capture 36.63%, 8.33% yield, vitamin C 118.13 mg/g, protein 4.70%, minerals 1.86%, fat 0.30%, 0.27% fiber, light beige-colored and has air bubbles on the surface micrograph of powder. The results of this study is expected to be a reference in the development of Aloe vera powder manufacturing industry. Keywords: aloe vera powder, filler (maltodextrin), foaming agent (tween 80), foam-mat drying